Effect of Dissemination of 2,4-Dichlorophenoxyacetic Acid (2,4-D) Degradation Plasmids on 2,4-D Degradation and on Bacterial Community Structure in Two Different Soil Horizons - Dejonghe, Winnie (American Society for Microbiology, 2000)
Transfer of the 2,4-dichlorophenoxyacetic acid (2,4-D) degradation plasmids pEMT1 and pJP4 from an introduced donor strain, Pseudomonas putida UWC3, to the indigenous bacteria of two different horizons (A horizon, depth of 0 to 30 cm; B horizon, depth of 30 to 60 cm) of a 2,4-D-contaminated soil was investigated as a means of bioaugmentation. When the soil was amended with nutrients, plasmid transfer and enhanced degradation of 2,4-D were observed. These findings were most striking in the B horizon, where the indigenous bacteria were unable to degrade any of the 2,4-D (100 mg/kg of soil) during at least 22 days but where inoculation with either of the two plasmid donors resulted in complete 2,4-D degradation within 14 days. In contrast, in soils not amended with nutrients, inoculation of donors in the A horizon and subsequent formation of transconjugants (10(5) CFU/g of soil) could not increase the 2,4-D degradation rate compared to that of the noninoculated soil. However, donor inoculation in the nonamended B-horizon soil resulted in complete degradation of 2,4-D within 19 days, while no degradation at all was observed in noninoculated soil during 89 days. With plasmid pEMT1, this enhanced degradation seemed to be due only to transconjugants (10(5) CFU/g of soil), since the donor was already undetectable when degradation started. Denaturing gradient gel electrophoresis (DGGE) of 16S rRNA genes showed that inoculation of the donors was followed by a shift in the microbial community structure of the nonamended B-horizon soils. The new 16S rRNA gene fragments in the DGGE profile corresponded with the 16S rRNA genes of 2,4-D-degrading transconjugant colonies isolated on agar plates. This result indicates that the observed change in the community was due to proliferation of transconjugants formed in soil. Overall, this work clearly demonstrates that bioaugmentation can constitute an effective strategy for cleanup of soils which are poor in nutrients and microbial activity, such as those of the B horizon.